Relationships of local lithium concentrations in drinking water to regional suicide rates in Italy. (17th November 2015) - Pompili, Maurizio; Vichi, Monica; Dinelli, Enrico; Pycha, Roger; Valera, Paolo; Albanese, Stefano; Lima, Annamaria; De Vivo, Benedetto; Cicchella, Domenico; Fiorillo, Andrea; Amore, Mario; Girardi, Paolo; et al.
Abstract : Objectives . Higher natural concentrations of lithium in drinking water may be associated with lower local rates of suicide. Methods . Lithium concentrations in drinking water were assayed by mass spectrometry at 145 sites in Italy, and compared with reported local suicide rates for men and women between 1980 and 2011. Results . Lithium concentrations in drinking water averaged 5.28 [CI: 4.08–6.48] μg/L (0.761 [0.588–0.934] μEq/L) and ranged from 0.110 to 60.8 μg/L (1.58 to 8.76 μEq/L). Lithium concentrations and local suicide rates were not significantly inversely related, except in 1980–1989, particularly among women. Conclusions . A proposed association between trace lithium concentrations in drinking water and risk of suicide was only partially supported, and mechanisms for potential clinical effects of trace levels of lithium are unknown.